2007
DOI: 10.1158/0008-5472.can-06-3585
|View full text |Cite
|
Sign up to set email alerts
|

c-FLIP: A Key Regulator of Colorectal Cancer Cell Death

Abstract: c-FLIP is an inhibitor of apoptosis mediated by the death receptors Fas, DR4, and DR5 and is expressed as long (c-FLIP L ) and short (c-FLIP S ) splice forms. We found that small interfering RNA (siRNA)-mediated silencing of c-FLIP induced spontaneous apoptosis in a panel of p53 wild-type, mutant, and null colorectal cancer cell lines and that this apoptosis was mediated by caspase-8 and Fas-associated death domain. Further analyses indicated the involvement of DR5 and/or Fas (but not DR4) in regulating apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
108
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(119 citation statements)
references
References 40 publications
9
108
0
2
Order By: Relevance
“…In addition, we found that FLIP promotes resistance to chemotherapy, as FLIP gene silencing enhanced chemotherapy-induced cell death in vitro, and FLIP L overexpression conferred resistance to chemotherapeutic agents both in vitro and in vivo (Longley et al, 2006;Wilson et al, 2007). We and others have found that FLIP overexpression renders cells resistant to death ligands (Jonsson et al, 2003;Longley et al, 2006), whereas FLIP downregulation increases sensitivity (Yeh et al, 2000;Mathas et al, 2004;Galligan et al, 2005;Longley et al, 2006).…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…In addition, we found that FLIP promotes resistance to chemotherapy, as FLIP gene silencing enhanced chemotherapy-induced cell death in vitro, and FLIP L overexpression conferred resistance to chemotherapeutic agents both in vitro and in vivo (Longley et al, 2006;Wilson et al, 2007). We and others have found that FLIP overexpression renders cells resistant to death ligands (Jonsson et al, 2003;Longley et al, 2006), whereas FLIP downregulation increases sensitivity (Yeh et al, 2000;Mathas et al, 2004;Galligan et al, 2005;Longley et al, 2006).…”
Section: Discussionmentioning
confidence: 60%
“…FLIP has been found to be overexpressed in many human cancers (Ryu et al, 2001;Zhou et al, 2004;Valnet-Rabier et al, 2005), and has emerged through our work and that of others, as a potential anti-cancer drug target (Hyer et al, 2005;Wilson et al, 2007). Furthermore, XIAP has been found to be overexpressed in several cancers, and small molecule and antisense approaches to target XIAP are in development (Hu et al, 2003;LaCasse et al, 2006).…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations